Apakah Benar Uang Tidak Dapat Dikendalikan Penggunaannya? Peran Financial planning Dan Financial Behavior melalui Pengendalian Social Shopping - Devon Shawa Situmorang; Rolyana Ferinia (Journal on Education, 2023)
This research wants to find out whether there is an influence between the variables of financial planning, Social Shopping and Financial Behavior. This research is directed at students and sees whether student Financial Behavior is good enough which is influenced by financial planning and Social Shopping carried out. This research method uses a quantitative approach with a correlational design. The correlational design seeks to investigate the values of two or more variables and test or determine the relationships or interrelationships that exist between them in a particular environment. There is a not very strong influence between Financial planning and Social Shopping, there is a weak influence between Financial planning and Financial Behavior, there is a strong influence between Social Shopping and Financial Behavior and the mediating variable Social Shopping has a moderate influence on financial planning and Financial Behavior. Our findings suggest that Social Shopping can be a stimulator of financial planning and Financial Behavior.